Parametric Study on the Compact G Shaped Monopole Antenna for 2.4 GHz and 5.2 GHz Application - Ahmad, B. H.; Ariffin, M. M.; Hassan, Nornikman; Roslan , M. N. S.; Abd Aziz, M. Z. A.; M. A., Atiqa; A. R. , Ayuni; Y. W., Ming; Y. P., Yin (Published by: Engg Journals Publications, 2013)
Abstract—This paper describes the design of a compact printed microstrip G-shaped monopole antenna for wireless local area network (WLAN application). The antenna has G-shaped resonating element which is designed for the two resonance frequencies at 2.4GHz and 5.2GHz respectively, which are the operating bands for WLAN application. The antenna is constructed by a non-conductor backed G-shaped strip with a mircostrip feed line. The dual band performance can be easily achieved by finetuning the length of the resonant path. The antenna is designed and simulated by using Computer Simulation Technology (CST) Studio simulation software. The parametric study with five different ground lengths had been done using parametric sweep. The the measurement results will be compared and analyzed with the simulated antenna.